2006
DOI: 10.1016/j.neuroimage.2005.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Processing stages underlying word recognition in the anteroventral temporal lobe

Abstract: The anteroventral temporal lobe integrates visual, lexical, semantic and mnestic aspects of wordprocessing, through its reciprocal connections with the ventral visual stream, language areas, and the hippocampal formation. We used linear microelectrode arrays to probe population synaptic currents and neuronal firing in different cortical layers of the anteroventral temporal lobe, during semantic judgments with implicit priming, and overt word recognition. Since different extrinsic and associative inputs prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 66 publications
7
61
0
Order By: Relevance
“…The closest coupling of BOLD and comprehensibility changes appeared deep in the medial and anterior sections of the temporal lobe (Fig. 5A), regions supposedly involved in semantic retrieval processing (Devlin et al, 2002;Halgren et al, 2006). Another striking parallel was the increased efficacy of frequency spectrum: not only were spectral changes more powerful in driving the measured BOLD changes, they also yielded steeper changes in participants' comprehension ratings.…”
Section: Discussionmentioning
confidence: 85%
“…The closest coupling of BOLD and comprehensibility changes appeared deep in the medial and anterior sections of the temporal lobe (Fig. 5A), regions supposedly involved in semantic retrieval processing (Devlin et al, 2002;Halgren et al, 2006). Another striking parallel was the increased efficacy of frequency spectrum: not only were spectral changes more powerful in driving the measured BOLD changes, they also yielded steeper changes in participants' comprehension ratings.…”
Section: Discussionmentioning
confidence: 85%
“…Further evidence that perirhinal cortex plays a role in written word processing comes from invasive electrophysiological studies in humans (Nobre and McCarthy, 1995). Local field potential recordings, current source density analysis and single neuron recording in human perirhinal cortex indicate that during judgement of real-life size, familiarity or concreteness as well as during overt word recognition, written words evoke distinct effects in perirhinal cortex (Halgren et al, 2006;Chan et al, 2011). 4.4 No detectable semantic similarity effect for spoken word modality A priori we had expected that left perirhinal cortex would also exhibit a semantic similarity effect for the spoken word modality, in agreement with a putative role in amodal semantic processing. As mentioned above, in the Fairhall and Caramazza (2013) study RSA revealed semantic similarity effects for both written words and pictures in ventral temporal cortex, indicative for commonality at least between visual input modalities.…”
Section: Extracting Meaning From Printed Wordsmentioning
confidence: 99%
“…These studies are typically done on rat or cat in in vitro preparations. However, laminar-electrode recordings have been done in awake macaques (Schroeder et al 1998) and even humans (Halgren et al 2006;Ulbert et al 2001Ulbert et al , 2004Wang et al 2005). Thus LPA, combined with template-fitting analysis, offers opportunities for deeper insights into the functional synaptic connections even for these systems.…”
Section: Implications Of Workmentioning
confidence: 99%